O-018 Single Institution Experience with Two Flow Diverters: A Head to Head Comparison. (29th July 2016) - Paul, A; Dalfino, J; Yamamoto, J; Boulos, A
Abstract : Introduction: There has been an increasing use of flow diverting stents in the endovascular management of intracranial aneurysms which previously would have been considered difficult to treat. Currently there are two flow diverting stents available in the United States. The Pipeline Embolization Device TM (Covidien) was approved by the FDA in 2011 and the Flow Redirection Endoluminal Stent (FRED TM, MicroVention) is currently involved in a clinical trial. There have been no comparisons of the two devices to date. Materials and methods: Patients treated with any means of Flow Diversion over a 2 year period were identified. Records and images were reviewed retrospectively. Statistics were calculated in Excel. Results: Twenty one aneurysms were treated in 19 patients using the FRED stent and 42 aneurysms were treated in 36 patients using a Pipeline stent. The age of the FRED patients was significantly higher than the Pipeline patients. There was no difference between in other demographic characteristics (Table 1 ). Conclusion: We present a single institutional experience with two flow diverting stents. There was no significant difference in neurological morbidity or mortality. There was a trend towards a higher rate of complete occlusion with the FRED device. There was no significant difference between the complication rates for the two groups, including ipsilateral ischemic stroke, ipsilateral ICH, aneurysm rupture and overall neurological morbidity and mortality. There was no significant difference in occlusion rate between the two groups. There was a trend towards a higher rate of complete occlusion in the FRED group but this was not statistically significant (p = 0.17). When only saccular aneurysms were evaluated, the complete occlusion rate in the FRED group was 92.3% and 70% in the pipeline group (p = 0.2). Disclosures: A. Paul: None. J. Dalfino: None. J. Yamamoto: None. A. Boulos: None.